Perspectives of Pharmacists Towards Patient-Centred Mental Health Pharmacy Services: A Focus Group Study - Nurul Aziera A Rahim; Norny Syafinaz Ab Rahman; Khairul Azrul Abdul Rahman; Jia Yi Cheong; Nur Fazlin Abd Ghafar; Yasmin Ibrahim; Aida Roziana Ramlan; Syahrir Zaini (Journal of Pharmacy)
Introduction: The rising prevalence of mental illness is a growing concern. Integrating pharmacists into mental health care teams could help address this challenge by improving service quality and accessibility for patients. This study investigates pharmacists' opinions regarding treatment care in the Kuantan and Pekan areas and their attitudes toward patient-centred mental health pharmacy services.  Methods: A qualitative study was conducted with 63 pharmacists around Kuantan and Pekan, Pahang, utilising a focus group discussion (FGD) style. The pharmacists were selected through purposive sampling from 2 general hospitals, 2 district health offices, and 1 teaching hospital. All locations are primary healthcare in Malaysia. The focus group topic guide was created using the relevant literature research. The entire interviews were audio-recorded and then transcribed verbatim. Thematic analysis was performed inductively to analyse the data. Results: This study involved 14 focus group sessions with all 63 pharmacists participating. Every interview was in person at the designated sites. From the interviews, 6 key themes were identified. 1. Role of pharmacists in mental health care. 2. Pharmacists-patients’ interactions. 3. Interprofessional collaborations with other healthcare workers. 4. Challenges and barriers. 5. Training needs for pharmacists and lastly 6. Improvement on the role of pharmacists and future practice. Conclusion: This research explores Malaysian pharmacists' perspectives on mental health treatments. It highlights pharmacists' potential contributions to mental health care, the challenges they face when assisting patients with mental health conditions, and the current limitations of mental health services in Malaysia's primary healthcare settings, hospitals, and Klinik Kesihatan.